2013
DOI: 10.1017/s0266467413000059
|View full text |Cite
|
Sign up to set email alerts
|

Forest dynamics of a subtropical monsoon forest in Dinghushan, China: recruitment, mortality and the pace of community change

Abstract: Abstract:Structure and demographics in many tropical forests is changing, but the causes of these changes remain unclear. We studied 5 y (2005–2010) of species turnover, recruitment, mortality and population change data from a 20-ha subtropical forest plot in Dinghushan, China, to identify trends in forest change, and to test whether tree mortality is associated with intraspecific or interspecific competition. We found the Dinghushan forest to be more dynamic than one temperate and two tropical forests in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 39 publications
(85 reference statements)
1
30
0
1
Order By: Relevance
“…In this situation, competitive interactions will exclude all but the tallest species, and then drive clustering. This may occur in specific regions of a homogeneous habitat where niche differences are not significant, but may not occur in a community with complicated habitats such as the DHS plot (Shen et al 2013, Wang et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this situation, competitive interactions will exclude all but the tallest species, and then drive clustering. This may occur in specific regions of a homogeneous habitat where niche differences are not significant, but may not occur in a community with complicated habitats such as the DHS plot (Shen et al 2013, Wang et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The 20-ha DHS plot was established in the core of the DHS Natural Reserve in 2005(Bin et al 2012. All stems with a diameter at breast height (dbh) ࣙ1 cm were measured, mapped and tagged in the initial census (Shen et al 2013). A total of 178 species and 61,125 individuals were recorded in the second census in 2010.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…relative growth rate of stem diameter (rgr; cm cm −1 year −1 ) was calculated as (log(DBH t )−log(DBH o ))/t, where DBh o and DBh t represent DBh at the first and last census, respectively (Poorter et al 2008). Calculations of rgr were done only for species that had at least 20 individuals in each size class during the initial census (Poorter et al 2008;shen et al 2013), resulting in 57 and 29 species for saplings and large trees, respectively.…”
Section: Study Site and Census Datamentioning
confidence: 99%
“…As Shen et al (2013) reported, this distribution can suggest recruitment stability, whereas bell-shaped distributions indicate a decline or lack of recruitment. However, different distribution shapes can also appear from different forest typologies (SHEN et al, 2013).…”
Section: Diameter Distributionmentioning
confidence: 60%